2022
DOI: 10.1182/bloodadvances.2022007444
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation by SARS-CoV-2 implicates the release of active tissue factor by infected cells

Abstract: Platelets are hyper-activated in COVID-19. However, the mechanisms promoting platelet activation by SARS-CoV-2 are not well understood. This may be due to inherent challenges at discriminating the contribution of viral versus host components produced by infected cells. This is particularly true for enveloped viruses and extracellular vesicles, as they are concomitantly released during infection and share biophysical properties. To study this, we evaluated whether SARS-CoV-2 itself, or components derived from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 82 publications
1
47
0
Order By: Relevance
“…Considering that endothelial cells can be infected by SARS-CoV-2 (39) and that multiple inflammatory cytokines are produced in response to infection, the observation that TF expression is induced during SARS-CoV-2 infection is not without surprise. In fact, a recent report further indicates that TF is released during SARS-CoV-2 infection, triggering platelet activation in the presence of residual amounts of plasma (40). D-dimer concentration in blood was maximal on day 1 post-infection suggesting that clotting issues were occurring very soon after infection.…”
Section: Discussionmentioning
confidence: 93%
“…Considering that endothelial cells can be infected by SARS-CoV-2 (39) and that multiple inflammatory cytokines are produced in response to infection, the observation that TF expression is induced during SARS-CoV-2 infection is not without surprise. In fact, a recent report further indicates that TF is released during SARS-CoV-2 infection, triggering platelet activation in the presence of residual amounts of plasma (40). D-dimer concentration in blood was maximal on day 1 post-infection suggesting that clotting issues were occurring very soon after infection.…”
Section: Discussionmentioning
confidence: 93%
“…However, thrombin is not only a central enzyme involved in coagulation cascades but also a potent inducer of platelet activation ( 78 , 79 ). In a more recent study, the TF/thrombin pathway was found to be pivotal for platelet activation in an ex vivo SARS-CoV-2 infection model ( 80 ). The authors concluded that TF activity from SARS-CoV-2-infected cells activates thrombin, which signals to protease-activated receptors (PARs) on platelets ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, the TF/thrombin pathway was found to be pivotal for platelet activation in an ex vivo SARS-CoV-2 infection model ( 80 ). The authors concluded that TF activity from SARS-CoV-2-infected cells activates thrombin, which signals to protease-activated receptors (PARs) on platelets ( 80 ). Taken together, it is plausible to speculate that the key upstream pathway that promotes platelet activation during SARS-CoV-2 infection is inhibited by heparin through disturbing thrombin ligation to platelet Glycoprotein Ib (GP Ib) and PARs ( 78 , 80 ), whereby the anticipated antithrombotic effects of aspirin and P2Y12 inhibitors in the above trials were diluted.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many in vitro studies showing that platelets are activated in hospitalized patients with COVID‐19 pneumonia, 81 multiple trials in moderate COVID‐19 patients showed no benefit of add‐on antiplatelet therapy to anticoagulants in improving clinical outcomes and conversely increased bleeding risk 74,75 . The REMAP‐CAP trial in critically ill COVID‐19 patients compared the use of add‐on therapy with either low‐dose aspirin or clopidogrel or other P2Y 12 inhibitors and found no benefit in improving the primary outcome of survival and freedom from organ support at 21 days with the different classes of antiplatelet agents 82 .…”
Section: Hospitalized Critical Care Covid‐19 Populationsmentioning
confidence: 99%